Diseño y construcción de escalera plegable para bus tipo escalera que permita el ascenso y descenso de usuarios de hasta 150 kg para la empresa “chivas pachangueras”. (2021)
Currently, users who take a service on a ladder bus or (Chiva Turística) in Bogotá find it difficult to ascend and descend the Chiva due to the height of this type of vehicle, for this reason the owners of the Chivas have decided to condition the randomly shapes chairs, ladders or other portable objects in an unsafe way due to their instability, lack of rigidity or slipping of the objects used that can cause accidents at the time of their use by the occupants since they are not anchored to the structure of the vehicle. To meet this need and in order to improve and ensure users at the time of accessing this service, the following project will be carried out which consists of designing and building a folding ladder system for safe use in the ascent and descent of The occupants of a ladder bus, regardless of the type of user, their different ages, whether they are children, youth, adults, without distinction of gender, this mechanism will consist of interconnected links where each one of them will contain a platform, achieving a step shape to the user for their support, being supported to the structure of the vehicle will give security, firmness and confidence at the time of use. Additionally, this mechanism will not be visible in such a way that it does not alter the original design of the Chiva Turística, since when closed it will remain under the vehicle, this device will be easily accessible for anyone who wishes to operate it, being more practical when operated manually. at the user's convenience or request.